Differential Diagnosis of Rare Subtypes of Progressive Supranuclear Palsy and PSP-Like Syndromes—Infrequent Manifestations of the Most Common Form of Atypical Parkinsonism - Krzosek, Patrycja; Madetko, Natalia; Migda, Anna; Migda, Bartosz; Jaguś, Dominika; Alster, Piotr (Frontiers in Aging Neuroscience, 2022)
Presently, there is increasing interest in rare PSP (progressive supranuclear palsy) variants, including PSP-PGF (PSP-progressive gait freezing), PSP-PI (PSP-postural instability), PSP-OM (PSP-ocular motor dysfunction), PSP-C (PSP-predominant cerebellar ataxia), PSP-CBS (PSP-corticobasal syndrome), PSP-SL (PSP-speech/language disorders), and PSP-PLS (PSP-primary lateral sclerosis). Diagnosis of these subtypes is usually based on clinical symptoms, thus thorough examination with anamnesis remains a major challenge for clinicians. The individual phenotypes often show great similarity to various neurodegenerative diseases and other genetic, autoimmune, or infectious disorders, manifesting as PSP-mimicking syndromes. At the current stage of knowledge, it is not possible to isolate a specific marker to make a definite ante-mortem diagnosis. The purpose of this review is to discuss recent developments in rare PSP phenotypes and PSP-like syndromes.